Analysis of policies that ensure transition to a green economy in SME’s activity in Republic of North Macedonia - Hadzi Naumova-Mihajlovska K., Petroska Angelovska N. (BC PUBLISHING, 2021)
Green economy in SMEs in the Republic of North Macedonia is a new concept in the modern society and aims SMEs in its basic policy to recognize the impact of the business activity on the environment. Therefore, on that basis to adopt environmental elements and also independently create policies to protect the environment. The purpose of the paper is by analyzing all documents and programs relating to sustainable development, specifically, the policies that indirectly encourage and / or stimulate the development of the concept of green economy in the operation and functioning of SMEs, to see the institutional support for promotion and development of the concept of green economy in the Republic of North Macedonia. Namely, there is a general agreement that the concept of green economy is closely related to sustainable development. Specifically, the areas of operation of the green economy are economics and ecology, and the three pillars of sustainability are economy, ecology and society. Hence, given that in the Republic of North Macedonia, the green economy is a relatively new concept and there is no single document - strategy or program for development of the green economy, the analysis uses documents and programs related to sustainable development policies. The analysis has determined that there are certain documents that have given special attention to supporting the adoption of environmentally-friendly business practices, but a special document is needed that will clearly determine the policies for the development of this concept and will concisely align them with the growth and development of SMEs in the Republic of North Macedonia, more precisely, the policies for development of the concept of green economy to be incorporated in the activities of SMEs. The results of the analysis are the basis for summarizing certain recommendations and measures to improve the institutional and regulatory framework for the development and application of the concept of green economy in SMEs and the creation of conditions for their successful implementation.
Keywords: green economy, SME's development, environmental policy, Republic of North Macedonia